THE MAIN CHARACTER’S MENTAL STATE IN THE MOVIE THE UNINVITED - Prakoso, Dimas Ananto; Rosmaidar, Rosmaidar; Neisya, Neisya (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2021)
The aim of this study is to analyze the main character’s mental state in the movie The Uninvited using the theory of psyche and defense mechanism. This study used descriptive method. The first step of analyzing The Uninvited movie was observing the main character’s mental state from the beginning until the end of the story, determining the cause of the main character’s unstable mental state by using Freud’s psyche theory through the character’s dialogues and certain scenes, determining types of defense mechanisms deployed by the main character in the movie, the last is interpreting how the main character’s mental state affects the plot of the movie. The results of this study are the writer found three factors that trigger the unstable mental states; six types of defense mechanism the main character deployed, and the impact of the main character’s mental state.